Digital Preservation of Ethno-medicinal Knowledge: Oral Traditions of the Tharu Tribe in Lakhimpur Kheri, Uttar Pradesh—A Library and Information Science (LIS) Framework - Karan Jaiswal (Journal of Knowledge in Data Science and Information Management, 2026)
The Ethno-medicinal knowledge of the Tharu tribe in Lakhimpur Kheri is threatened by rapid urbanization. This study proposes an LIS-based digital institutional repository (DIR) to document their oral traditions through field surveys and interviews. By leveraging this framework, the research aims to preserve indigenous heritage for future pharmacological study and community identity. Key components of the framework include the use of multimedia documentation (audio/video), the implementation of knowledge management (KM) techniques, and addressing ethical concerns regarding intellectual property rights (IPR). The findings suggest that a structured LIS intervention can transform oral “hidden” knowledge into a “visible” digital resource, fostering community identity and providing a valuable database for pharmacological research.